2006
DOI: 10.1038/sj.gene.6364330
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental contributions to plasma C-reactive protein and interleukin-6 levels – a study in twins

Abstract: Elevated baseline levels of acute-phase proteins such as C-reactive protein (CRP) or cytokines like interleukin-6 (IL-6) are known risk factors for atherosclerosis and cardiovascular disease (CVD) events. However, until today, there is only controversial information about the contribution of genetic and environmental factors. Therefore, we performed an open prospective study in 108 monozygotic (MZ) and 60 same-sex dizygotic (DZ) twin pairs to analyse the genetic and environmental contributions to plasma CRP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 69 publications
4
47
2
2
Order By: Relevance
“…Heritability of serum hs-CRP concentration H Berrahmoune et al discrepancy between most of the previous familial and twin studies investigating the hs-CRP concentration heritability and our results, since they reported a significant and higher polygenic effect (between 20 and 52%) [8][9][10]12,13 (Table 5), while we found no genetic effect on hs-CRP concentration heritability. However, our results are in accordance with those of Friedlander et al 15 who reported no polygenic effect for hs-CRP concentrations and the changes of over 10 years.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Heritability of serum hs-CRP concentration H Berrahmoune et al discrepancy between most of the previous familial and twin studies investigating the hs-CRP concentration heritability and our results, since they reported a significant and higher polygenic effect (between 20 and 52%) [8][9][10]12,13 (Table 5), while we found no genetic effect on hs-CRP concentration heritability. However, our results are in accordance with those of Friedlander et al 15 who reported no polygenic effect for hs-CRP concentrations and the changes of over 10 years.…”
Section: Discussioncontrasting
confidence: 99%
“…In twin studies, within-pair correlations were even higher: 0.40-0.49 and 0.17-0.28, for MZ, 9,10,30 and DZ twins, 9,10 respectively. In addition, there is a Tables A2 and A3 in online appendix.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The most parsimonious model is printed in bold. Jermendy et al, 2011;MacGregor et al, 2004;Rahman et al, 2009;Reed et al, 1994;Sas et al, 2012;Su et al, 2008Su et al, , 2009aSu et al, , 2009bWang et al, 2011;Wessel et al, 2007;Worns et al, 2006) and extend the findings of previous studies by showing that genetic non-additivity is an important factor in explaining individual differences in TNF-␣, CRP, and fibrinogen levels and by ruling out a large role for environmental factors shared by family members.…”
Section: Discussionsupporting
confidence: 86%
“…3 A large proportion of this heritability can be explained by the IL6R polymorphism, rs2228145 (previously rs8192284 or D358A), which affects both circulating soluble IL-6R and IL-6 levels, 4-6 but this does not account for all the reported heritability (up to 0.61). 7 The IL6 promoter has been extensively studied in terms of both transcription factor binding and genetic variation, with a number of well-characterised polymorphisms identified in the proximal promoter, including rs1800795 ( À 174G4C), rs1800796 ( À 572G4C) and rs1800797 ( À 597G4A). Despite the numerous association studies with these single-nucleotide polymorphisms (SNPs), and studies on in vivo circulating IL-6 levels, in vitro gene expression and luciferase reporter assays (reviewed in Smith and Humphries 3 ), there is no conclusive evidence of IL6-SNP functionality.…”
Section: Introductionmentioning
confidence: 99%